The role of text-books and ICT in designing and implementing effective lessons: examining curriculum recommendations and teachers’ practices - Khalid, Madihah (2011)
Teachers in Brunei Darussalam generally use recommended textbooks and books supplied by the Ministry of Education in order to teach their students. Many of them only rely on those books while there are others who would look at other books or surf the internet in order to get ideas on how best to teach a mathematics topic. Some would follow the recommendations entirely, but many would change the recommended lessons to adapt to their classrooms. This paper would examine the recommendations of the new SPN 21 (New Education System of the 21st Century) mathematics curriculum and the normal practice by the teachers in this country in order to design and implement effective lessons.